A Crystalline Ready-to-Use Form of Cyclopentadiene - Krupp, Felix; He, Shiliang; Frey, Wolfgang; Richert, Clemens (Synlett, 2018)
Cyclopentadiene (Cpd) is widely used as a starting material in organic and inorganic chemistry. In neat form, Cpd dimerizes, making it necessary to distill it prior to use to obtain fully reactive material. We have screened three different tetraphenyladamantane octaethers for their ability to act as encapsulating organic crystal (EnOC) hosts for Cpd. To this end, we also synthesized 1,3,5,7-tetrakis(3,5-dimethoxyphenyl)adamantane, a new octaether, dubbed iso-TDA. Only one of the octaethers was found to produce inclusion complexes with Cpd in the crystalline state. The encapsulated diene was stable for one month and showed full reactivity in a series of different synthetic transformations.
Keywords: cycloadditions; cyclopentadiene; inclusion complexes; uptake and release; X-ray crystal structure